2021
DOI: 10.3389/fneur.2021.646928
|View full text |Cite
|
Sign up to set email alerts
|

Distinct MicroRNA Profiles in the Perilymph and Serum of Patients With Menière's Disease

Abstract: Hypothesis: Menière's disease microRNA (miRNA) profiles are unique and are reflected in the perilymph and serum of patients.Background: Development of effective biomarkers for Menière's disease are needed. miRNAs are small RNA sequences that downregulate mRNA translation and play a significant role in a variety of disease states, ultimately making them a promising biomarker. miRNAs can be readily isolated from human inner ear perilymph and serum, and may exhibit disease-specific profiles.Methods: Perilymph sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 47 publications
0
17
1
Order By: Relevance
“…Previous studies have identified endolymphatic hydrops in these patients. However, the pathophysiological mechanisms are not yet fully understood, although genetic, vascular, immunological origin, the aberrant expression of aquaporins, or a combination of causes have been proposed [ 27 ]. Several research teams have been interested in identifying biomarkers and mechanisms in this pathology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have identified endolymphatic hydrops in these patients. However, the pathophysiological mechanisms are not yet fully understood, although genetic, vascular, immunological origin, the aberrant expression of aquaporins, or a combination of causes have been proposed [ 27 ]. Several research teams have been interested in identifying biomarkers and mechanisms in this pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Several research teams have been interested in identifying biomarkers and mechanisms in this pathology. Using miRNA profiles, some authors found altered perilymph linked with Ménière’s disease, which could serve as a potential biomarker [ 27 ]. Proteonomic analysis has allowed for the identification of protein short-chain dehydrogenase/reductase family 9C member 7 in perilymph from patients with Ménière’s disease [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…As EH has been proposed to result from a disturbance in endolymphatic volume regulation that is associated with changes in the microenvironment of luminal fluid of the ES (12), understanding the molecular pathomechanism(s) underpinning the regulation of the immune reaction in the luminal fluids of ES is important both for furthering our knowledge of the physiopathology of EH and for identifying biomarkers for diagnosis or prognosis of pathologies of the MD. Recently, there has been a growing interest in developing a "liquid biopsy" of the inner ear as a surrogate for tissue biopsy to identify molecular biomarkers (13)(14)(15)(16). Proteomics analysis in samples of perilymph (13) and ES luminal fluid (ELF) (14,15) from patients with MD and controls suggested that increased inflammatory reactions Abbreviations: MD, Meniere's disease; EH, endolymphatic hydrops; ES, endolymphatic sac; ELF, ES luminal fluid; AN, acoustic neuroma; EDB, endolymphatic duct blockage; TNF-α, tumor necrosis factor α; IFN-γ, interferon-γ; IL, interleukin; Simoa, single-molecular array; RGP, resorufin β-D-galactopyranoside; PBST, triton-phosphate buffered saline; DAPI, 4 ′ ,6diamidino-2-phenylindole; ANOVA, analysis of variance; IF, immunofluorescence; SNHL, sensorineural hearing loss.…”
Section: Introductionmentioning
confidence: 99%
“…As EH has been proposed to result from a disturbance in endolymphatic volume regulation that is associated with changes in the microenvironment of luminal fluid of the ES ( 12 ), understanding the molecular pathomechanism(s) underpinning the regulation of the immune reaction in the luminal fluids of ES is important both for furthering our knowledge of the physiopathology of EH and for identifying biomarkers for diagnosis or prognosis of pathologies of the MD. Recently, there has been a growing interest in developing a “liquid biopsy” of the inner ear as a surrogate for tissue biopsy to identify molecular biomarkers ( 13 16 ). Proteomics analysis in samples of perilymph ( 13 ) and ES luminal fluid (ELF) ( 14 , 15 ) from patients with MD and controls suggested that increased inflammatory reactions in the inner ear may contribute to the pathology of MD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation